Application of embedded fibre Bragg grating sensors for structural health monitoring of complex composite structures for marine applications. (March 2021) - Mieloszyk, Magdalena; Majewska, Katarzyna; Ostachowicz, Wieslaw
Abstract: Fibre reinforced polymer (FRP) materials are recently widely applied in the marine industry. The high popularity of composites and safety requirements results in the development of Structural Health Monitoring (SHM) systems. One of the sensors types that can be permanently integrated with a composite structure and used as a part of SHM system are fibre Bragg grating (FBG) sensors. Among FBG sensors advantages small size, high corrosion resistance, and absence of electric current are especially important in monitoring of composite marine structures. The paper presents an application of embedded FBG sensors arrays for evaluation of complex composite structure — a fast patrol boat. The experimental investigations contain spectra analyses for thin laminate sample (skin), a composite sandwich panel and fast patrol boat hull (sandwich structure). The quality of sensors spectra (before/after embedding and loading) was determined using the Pearson correlation coefficient. The relationship between strain and temperature in exploitation range was determined for laminate and sandwich structures. A linear relationship was achieved for both elements. The relationship for the sandwich panel was then applied during strain analyses of the boat composite hull. The utility of designed FBG sensors array for the panel was also verified by sensors responses on impact excitation in chosen points on the structure. The achieved results were then used during designing FBG sensors array embedded into the hull. FBG sensors spectra deformations due to fast patrol boat hull manufacturing process and exploitation as well as strain curves determined for the boat during tests at dry dock and at sea trials are analysed. Highlights: Problems of designing SHM system based on embedded FBG sensors for composite boat. Embedded FBG sensors quality determined by the Pearson correlation coefficient. Spectra deformations due to hull manufacturing and exploitation were analysed. Strain curves for the boat tests (dry dock, sea trials) are presented.